A Decade of Dinuclear Technetium Complexes with Multiple Metal–Metal Bonds. Issue 27 (24th June 2014) - Poineau, Frederic; Forster, Paul M.; Todorova, Tanya K.; Johnstone, Erik V.; Kerlin, William M.; Gagliardi, Laura; Czerwinski, Kenneth R.; Sattelberger, Alfred P.
Abstract: Transition metal complexes with multiple metal–metal bonds exhibit interesting catalytic and biological properties. One element whose metal–metal bond chemistry has been poorly studied is technetium. Currently, only 25 technetium complexes with multiple metal–metal bonds have been structurally characterized. The nature of metal–metal interactions in these complexes, as well as the influence of ligands on the bonding in the Tc2 n + unit ( n = 6, 5, 4) are not well understood. In order to better understand the influence of ligands on the Tc–Tc bonding, a study of the solid‐state and electronic structure of dinuclear complexes with the Tc2 n + unit ( n = 6, 5, 4) has been performed. Dinuclear technetium complexes ( n Bu4 N)2 Tc2 X8, Tc2 (O2 CCH3 )4 X2, Tc2 (O2 CCH3 )2 Cl4, cesium salts of Tc2 X8 3–, and Tc2 X4 (PMe3 )4 (X = Cl, Br) were synthesized; their molecular and electronic structures, as well as their electronic absorption spectra, were studied by a number of physical and computational techniques. The structure and bonding in these systems have been investigated by using multiconfigurational quantum calculations. For all these complexes, the calculated geometries are in very good agreement with those determined experimentally. Bond order analysis demonstrates that all these complexes exhibit a total bond order of approximately 3. Analysis of individual effective bond order (EBO) components shows that these complexes have similar σ components, while the strength of their π components follows the order Tc2 X4 (PMe3 )4 > Tc2 X8 3– > Tc2 (O2 CCH3 )2 Cl4 > Tc2 X8 2– . Calculations indicate that the δ components are the weakest bond in Tc2 X8 n – ( n = 2, 3) and Tc2 (O2 CCH3 )2 Cl4 . Further analysis of Tc2 X8 3– and Tc2 X4 (PMe3 )4 (X = Cl, Br) indicates that the electronic structure of the Tc2 5+ and Tc2 4+ units is insensitive to the nature of the coordinating ligands. The electronic absorption spectra of Tc2 X8 n – ( n = 2, 3), Tc2 (O2 CCH3 )2 Cl4, and Tc2 X4 (PMe3 )4 (X = Cl, Br) were studied in solution, and assignment of the transitions was performed by multiconfigurational quantum chemical calculations. For the Tc2 X8 n – ( n = 2, 3; X = Cl, Br) anions and Tc2 (O2 CCH3 )2 Cl4, the lowest‐energy band is attributed to the δ→δ* transition. For Tc2 X4 (PMe3 )4, the assignment of the transitions follow the following order in energy: δ*→σ* < δ*→π* < δ→σ* < δ→π*. Abstract : This review covers the metal–metal bond chemistry of dinuclear technetium complexes published in the period 2005–2014. The preparation, solid‐state and electronic structures, and spectroscopic properties of ( n Bu4 N)2 Tc2 X8, Tc2 (O2 CCH3 )4 X2, Tc2 (O2 CCH3 )2 Cl4, cesium salts of Tc2 X8 3–, and Tc2 X4 (PMe3 )4 (X = Cl, Br) are presented.